Fairness and Promises for Sale - Håkan J. Holm; Anders Daielson (Lund University, School of Economics and Management, Department of Economics, 2005)
While many studies have shown that fairness matters few efforts have been made to find out how important fairness is to the individual and thereby assessing the limits of these fairness concerns. This study reports on Trust game experiments in Sweden and Jamaica where subjects could forego a more fair allocation in return for extra money. The results indicate that 90 percent of subjects that had demonstrated fairness ambitions were willing to let down their counterparts if compensated. Explicit promises did not seem to matter. The first player was informed that the second player could earn extra money by changing to an unfair allocation. This modification appeared to make the trust aspect more salient which can explain a relatively strong consistency between trust behavior and answers to attitudinal trust questions.
Keywords: C91; D63; D64; 330; Experiments; trust game; fairness; inequality aversion; opportunism; promise